COHESION IN SPOKEN DISCOURSE: A DISCOURSE OF HARJAS SINGH SIDHU’S SPEECH ON THE PUBLIC SPEAKING ACADEMY YOUTUBE CHANNEL - Putri, I Gusti Ayu Vina Widiadnya; Dewi, Ni Komang Nira (UHN IGB Sugriwa Denpasar, 2025)
This study aims to analyze the cohesive devices used in Harjas Singh Sidhu’s speech on the Public Speaking Academy YouTube channel, addressing the problem of how cohesion contributes to the clarity and organization of spoken communication. The data were obtained from a recorded speech video, and the analysis applied a descriptive qualitative method. The instrument of this study was the researcher, supported by an observation sheet used to categorize each cohesive device. The data were collected through repeated viewing, transcription, and identification of cohesive elements, while the analysis involved classification, description, and interpretation of the findings. The results show that the speech contains two types of grammatical cohesion—Personal Reference and Demonstrative Reference—and two types of lexical cohesion—Reiteration (Repetition and Superordinate) and Collocation. No instances of Substitution and Ellipsis were found in grammatical cohesion, and no examples of Synonym or General Word occurred in lexical cohesion. Overall, the findings demonstrate that the use of cohesive devices supports the clarity, flow, and coherence of the speaker’s message. The novelty of this study lies in its focus on a high-performing non-native English speaker in a competitive public speaking context, offering insights into cohesion use in authentic, performance-based spoken discourse—an area that remains underexplored in previous research.